Proposed technique for fabricating complete denture - Abdulsalam Ali Zwiad (Wolters Kluwer Medknow Publications, 2012)
Introduction: Reduction of the visits for fabricating complete dentures are welcomed by both dentists and patients and this might be an aspect of the new changes in prosthodontic treatment according to the suggested new methods. Clinical Innovation: Complete dentures fabricated by the technique described in this report reduce processing time, cost and efforts since the technique does not require the use of gypsum materials, metal flasks or other related materials to obtain a mold for packing the heat cured acrylic resin as might be needed with the conventional method. This method requires only an appropriate volume of silicone impression material to provide the required mold and a heat pressure machine for processing and polymerization of the heat-cured acrylic resin. Although this technique might be difficult to be applicable by all dentist but it could be consider an advisable method. Discussion: Because the record base in this technique is made of heat cured resin, it provides a reliable denture base with better retention and stability and it overcomes the shortcomings that may be faced during registration of vertical dimension. This technique meets the basic requirements for a successful complete denture which is well tolerated by the patient's mouth.